The capacity of the fecal microbiota from Malawian infants to ferment resistant starch - Wang, Y.; Mortimer, E.K.; Katundu, K.G.H.; Kalanga, N.; Leong, L.E.X.; Gopalsamy, G.L.; Christophersen, Claus; Richard, A.C.; Shivasami, A.; Abell, G.C.J.; Young, G.P.; Rogers, G.B. (FRONTIERS MEDIA SA, 2019)
© Authors.